POTRET KOMPETENSI INTI USAHA KECIL MAKANAN KHAS BERBASIS TAPE SINGKONG DI KABUPATEN JEMBER - Moh. Miftahul Munir; Djoko Poernomo; Zahra Puspitaningtyas (Universitas Tribhuwana Tunggadewi, 2017)
Abstrak: Specific Food-based cassava tape is a food that became the heritage of the ancestors and give a pride because in it’s rich in art, creativity, and ideas. Various specific food products of an area also found many specific foods made from cassava tape and done by small businesses. Therefore it is necessary to maintain the existence of processed food products so that processed food products based on cassava tape have a sustainable competitive advantage. Sustained competitive advantage can be realized by finding the resources and capabilities that become core competencies so that the resulting product is unique and different from the competitors. The purpose of this paper is to explain the resources and capabilities of small-scale cassava tape-based food businesses that are the core competencies. Research location in Jember district of East Java province. The type of research used is qualitative research. Informants are small business owners of specific cassava tape based foods. Data collection is done by in-depth interviews and in-depth observations. Data analysis using descriptive analysis. The research findings show that the resources and capabilities of firms that are core competencies include human resources, experience resources, reputation resources, expertise resources, knowledge resources, and marketing capabilities. The core competencies are managed using the four management functions discussed in this paper. Keywords: Core Competence, Management, Small business, Cassava Tape.